There is no routine head and neck exam during the COVID‐19 pandemic. Issue 6 (21st April 2020) - Chan, Jason Y. K.; Tsang, Raymond K. Y.; Yeung, K. W.; Abdullah, Victor; Ku, Peter; Wong, Eddy W. Y.; Mehta, Nishchay; Orosco, Ryan K.; Holsinger, F. Christopher
Abstract: Head and neck examinations are commonly performed by all physicians. In the era of the COVID‐19 pandemic caused by the SARS‐CoV‐2 virus, which has a high viral load in the upper airways, these examinations and procedures of the upper aerodigestive tract must be approached with caution. Based on experience and evidence from SARS‐CoV‐1 and early experience with SARS‐CoV‐2, we provide our perspective and guidance on mitigating transmission risk during head and neck examination, upper airway endoscopy, and head and neck mucosal surgery including tracheostomy.